2013
DOI: 10.1371/journal.pone.0050961
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing of RNA from Ancient Maize Kernels

Abstract: The characterization of biomolecules from ancient samples can shed otherwise unobtainable insights into the past. Despite the fundamental role of transcriptomal change in evolution, the potential of ancient RNA remains unexploited – perhaps due to dogma associated with the fragility of RNA. We hypothesize that seeds offer a plausible refuge for long-term RNA survival, due to the fundamental role of RNA during seed germination. Using RNA-Seq on cDNA synthesized from nucleic acid extracts, we validate this hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Besides delivering ancient genomes and epigenomes, new methodological developments have also provided access to ancient transcriptomes 113,114 and proteomes 17,115,116 . Owing to the biochemical processes inherent in animal cell death, animal tissues are unlikely to represent good reservoirs for long-term RNA survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides delivering ancient genomes and epigenomes, new methodological developments have also provided access to ancient transcriptomes 113,114 and proteomes 17,115,116 . Owing to the biochemical processes inherent in animal cell death, animal tissues are unlikely to represent good reservoirs for long-term RNA survival.…”
Section: Discussionmentioning
confidence: 99%
“…Materials still exist in other organisms that do not undergo autolysis. One example is plant seed, a tissue that requires RNA survival for germination and that has demonstrated ancient RNA survival going back hundreds to thousands of years 113,114 . Such materials may contribute to our understanding of how gene expression pathways have been remodelled during domestication.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA from one species can comprise just 10 -8 percent of the total eDNA in freshwater (Turner et al 2014a); thus, low template quantity and background interference present challenges for functional genomic analysis of macrobial eDNA, particularly for single-copy nuclear loci (Morin et al 2007). However, paleogenetic studies have demonstrated that these types of functional genomic data can be obtained from biomaterial exposed to substantial DNA/RNA decay (Fordyce et al 2013). Furthermore, microbial metagenomics has paved the way for functional genomic analysis of eDNA, demonstrating how to analyze functional genomic data from complex environmental mixtures of individuals and species (Mendoza et al 2015).…”
Section: Functional Genetics and Genomicsmentioning
confidence: 99%
“…RNA is highly prone to hydrolytic attack relative to DNA, partly because of its single stranded nature. However, while more labile than DNA, ancient RNA still occurs in useful quantities (Fordyce et al, 2013;Smith et al, 2014a). Furthermore, methylation can be detected in archaeological samples (Briggs et (Palmer et al, 2012) mapped to Arabidopsis thaliana metabolic pathways.…”
Section: The Challenge Of Understanding How Plant Community Systems Bmentioning
confidence: 99%